FEATURES OF LOCATING BUS STATIONS AND BUS TERMINALS IN LARGE AND LARGEST CITIES - Stepanchuk, Oleksandr; Lapenko, Oleksandr; Chernyshova, Oksana (Theory and practice of design, 2024)
An analysis of the current state of existing bus stations and bus terminals in the cities of Ukraine has been conducted, revealing problems and drawbacks regarding their placement within the city area. Justification of existing trends regarding the use of urban street space and available parking lots for passenger disembarkation and boarding from suburban and intercity buses is provided. The aim of the study is to analyze the situation that has arisen in recent years in most cities of Ukraine regarding the organization of intercity and suburban transport connections. The article presents generalized results of the current state of the street-road network of cities and its impact on the conditions of operation of external passenger automobile transport. Methodology. Research methods: analysis of literary sources, materials related to the placement of bus stations and bus terminals in large and largest cities. Results. The main approaches to locating bus stations and bus terminals in large and largest cities are proposed, based on the principles of providing convenience, comfort, and safety for passengers. The main factors influencing the determination of the appropriateness of the chosen location for the bus station or bus terminal on the territory of a settlement were considered, including: transport accessibility, condition and traffic conditions of the street-road network, capacity of the street-road network of the city, possibility of convenient transfer to urban rapid transport, capacity of urban rapid transport, existing passenger flow in the respective direction of movement, complexity of the network of routes of urban passenger transport, correspondence of the area size to the maximum volume of passenger flow at the bus station, land value and cost, compliance with its urban planning requirements and limitations. Practical significance. The practical value of this study lies in identifying and highlighting problems associated with the inefficient operation of bus stations and bus terminals in cities, namely, their inappropriate placement on the territory of a specific settlement, which corresponds to the requirements of sustainable development and the formation of a comfortable urban environment.